2009
DOI: 10.1063/1.3253400
|View full text |Cite
|
Sign up to set email alerts
|

On fully nonlinear, vertically trapped wave packets in a stratified fluid on the f-plane

Abstract: The ubiquity of solitary and solitarylike internal waves in the coastal ocean has been recognized for some time. Recent theoretical studies of a strongly nonlinear, weakly nonhydrostatic set of layer-averaged model equations have predicted that rotation, for example, on the f-plane, can lead to the decay and subsequent reemergence of internal solitary waves. We reconsider this problem using high resolution numerical simulations of the rotating stratified Euler equations. We find that in certain cases the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Several numerical experiments of model equations, including the Ostrovsky equation (see equation (6) below), and of fully nonlinear equation systems have shown that background rotation tends to inhibit the production of internal solitary waves, see Helfrich 9 , Grimshaw and Helfrich 6,7 , and Stastna et al 16 , and the references therein. In particular, Helfrich 9 found that an initial solitary wave disturbance decayed through the radiation of inertial gravity waves, and eventually an envelope wave packet formed.…”
Section: The Solitary Wave Solution Ismentioning
confidence: 99%
“…Several numerical experiments of model equations, including the Ostrovsky equation (see equation (6) below), and of fully nonlinear equation systems have shown that background rotation tends to inhibit the production of internal solitary waves, see Helfrich 9 , Grimshaw and Helfrich 6,7 , and Stastna et al 16 , and the references therein. In particular, Helfrich 9 found that an initial solitary wave disturbance decayed through the radiation of inertial gravity waves, and eventually an envelope wave packet formed.…”
Section: The Solitary Wave Solution Ismentioning
confidence: 99%
“…Motivated by the results presented in Stastna et al (2009), a domain 4 times longer than the physical tank (Lx = 52 m) was used, as 13 m is an insufficient length when considering lower (closer to physical) rotation rates. In addition to this it was decided to change the tank depth to a more evenly divisible 0.4 m (from a laboratory value of 0.36 m).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they also performed collision experiments, finding that the packets that emerge from the initial solitary waves can merge during collisions and hence do not interact as classical solitons. Finally, Stastna et al (2009) also found that by increasing the width of a flat-crested wave, more energy was deposited into the tail. It remains to reconcile the two sets of results in detail, likely by systematically reducing the solitary wave amplitude used as an initial condition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations